Implementasi Metode Tabulasi Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Tumbukan Sentral - Akhmad Rosyidan Rifaldi; Mohammad Fathorrosi; Bambang Supriadi; Ulfa Mazidah; Sofia Ratnaningsih; Pretty Shintyaningrum; Siti Nur Afitah (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2023)
Central collision is one of the physics subjects taught in high school. Where this material is related to mathematical equations so that students' mathematical abilities must be good. research to study students' cognitive learning outcomes in solving central collision questions using the tabulation method. This research was conducted at MAN 1 Jember using class X MIPA 1 . Based on the research that has been done, the average value of the students' pretest before being given treatment is 30.9 and the average value of students' posttest after being given treatment is 69.2. The increase in pre-test and post-test results shows that the tabulation method can improve student learning outcomes in the central collision material with an n-gain value of 0.56 which is included in the medium category. The results of interviews related to student responses showed that the tabulation method was preferred by students, and students were satisfied in applying it in solving central collision questions.